Clues to the presence of pathogenic fungi in certain environments - Restrepo, A.; Baumgardner, D. J.; Bagagli, E.; Cooper, C. R.; McGinnis, M. R.; Lazera, M. S.; Barbosa, F. H.; Bosco, SMG; Camargo, ZPF; Coelho, Kunie Iabuki Rabello [UNESP]; Fortes, S. T.; Franco, M.; et al. (B I O S Scientific Publishers Ltd, 2000)
The presence of various pathogenic fungi in rather unsuspected hosts and environments has always attracted the attention of the scientific community. Reports on the putative role of animals in fungal infections of humans bear important consequences on public health as well as on the understanding of fungal ecology. Fungi are ubiquitous in nature and their great capacity for adaptation allows them to survive and indeed, to thrive, in plants, trees and other natural substrata. Nonetheless, we are just beginning to learn the significance that these diverse fungal habitats have on the increasing number of immunosuppressed individuals. The accidental or permanent presence of fungi in animals, plants, soils and watercourses should not be taken too lightly because they constitute the source where potential pathogens will be contracted. If those fungal habitats that carry the largest risks of exposure could be defined, if seasonal variations in the production of infectious propagules could be determined, and if their mode of transmission were to be assessed, it would be possible to develop protective measures in order to avoid human infection. Additionally, unsuspected avenues for the exploration of fungal survival strategies would be opened, thus enhancing our capacity to react properly to their advancing limits. This paper explores several ecological connections between human pathogenic fungi and certain animals, trees, waterways and degraded organic materials. The occurrence of such connections in highly endemic areas will hopefully furnish more precise clues to fungal habitats and allow the design of control programs aimed at avoiding human infection.
Keywords: armadillos; bamboo rats; jungle trees; pathogenic fungi